Prophetic Communication in Digital Preaching: Building a Critical and Wise Society in Using Social Media/Komunikasi Profetik dalam Dakwah Digital: Membangun Masyarakat yang Kritis dan Bijak dalam Bermedia Sosial - Sakdiah, Halimatus; Rahmah, Mariyatul Nurhidayati; Adawiah, Rabiatul; Aslamiah, Rabiatul (Al-Hiwar Jurnal Ilmu dan Teknik Dakwah, 2025)
The development of various forms of social media has both positive and negative impacts on communication interactions including digital preaching. This is a challenge on how digital preaching on social media can run well. This paper aims to examine the role of prophetic communication, especially concerning the ethical values ​​of prophetic communication in digital preaching and its implementation to overcome the negative impacts of the development of social media. This research method uses a library study, using several related literatures, with content analysis. The findings of the research show that prophetic communication based on the nature of the Prophet (siddiq, amanah, tabligh, fathanah), and the integration of values ​​from the pillars of prophetic communication in the form of humanization values ​​(amar ma'ruf), liberation values ​​(nahi munkar) and transcendence values ​​(tu'minubillah), as well as the application of ethical principles of prophetic communication can develop ethical digital preaching, mutual respect, wise without violence, encourage and increase piety and build a society that is critical and wise in using social media.